Pendampingan Usaha Produk “Olahan Kentang” Mahasiswa Universitas Kristen Indonesia Toraja - Wilma Dian Ardiyanti; Yohanis Lotong Ta’dung; Ade Lisa Matasik; Yonaldes Qreistamara Sarunan Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The implementation of this service activity is carried out by providing material regarding the preparation of proposals and planning for a Potato Processed Food Products Business. The delivery of this training material is carried out by means of lectures and discussions. Assistance is provided by providing direction on how to start business planning, marketing and business development strategies, as well as preparing business proposals. The aim of this assistance is to foster and develop the entrepreneurial spirit at the Indonesian Christian University of Toraja so that students are increasingly interested in entrepreneurship. The form of activity is in the form of guidance in creating a business, such as determining a business idea first/determining the product to be sold, developing a business idea (market segmentation), marketing strategy, finance, and making a business proposal. After that, a business and product proposal presentation was carried out to find out to what extent the students were able to prepare a business proposal for processed potato products.